New Dammarane Triterpenes from the aerial parts of Ibicella lutea grown in Argentina - Simirgiotis, Mario Juan (2003)
Two new dammarane triterpenes have been isolated from the aerial parts of Ibicella lutea, 3-acetyl-24- epi-polacandrin (1) and 1,3-diacetyl-24-epi-polacandrin (2), and were obtained along with the known compounds 20S*,24S*-epoxy-3â,12â,25-trihydroxydammarane (3) and apigenin. The structures of compounds 1 and 2 were deduced by spectroscopic studies and by chemical transformations leading to the preparation of derivatives 4-11. The structure and relative stereochemistry of 1 were verified by single-crystal X-ray analysis. The natural compounds and selected semisynthetic derivatives were evaluated against several tumor cells.